2007
DOI: 10.1111/j.1365-2605.2007.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tyrosine kinases PDGFR and C‐Kit by imatinib mesylate interferes with postnatal testicular development in the rat

Abstract: The tyrosine kinase receptor c-kit and its interaction with the ligand, stem cell factor (SCF), play an essential role in the developing testis. C-kit is important for the development of the Leydig cells and for the migration, proliferation and survival of spermatogonia. Platelet-derived growth factor (PDGF) and its tyrosine kinase receptor (PDGFR) are important for the development of Leydig cells and myoid cells. The chemotherapeutic agent, imatinib mesylate (STI571, Glivec; Novartis) inhibits both of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 47 publications
3
51
1
4
Order By: Relevance
“…This time interval was selected to cover exactly the period of neonatal gonocyte proliferation and migration and to avoid the confounding effect on c-kit inhibition that may take place at later times. Indeed, Nurmio et al (40) reported that imatinib administration in P5-P7 rat blocked or delayed migration of gonocytes from the center of the seminiferous tubules to the basement membrane, delayed the formation of the germline stem cell pool, reduced proliferation of type A spermatogonia normally observed at P8, and induced germ cell apoptosis. They attributed all these events to the inhibition of c-kit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time interval was selected to cover exactly the period of neonatal gonocyte proliferation and migration and to avoid the confounding effect on c-kit inhibition that may take place at later times. Indeed, Nurmio et al (40) reported that imatinib administration in P5-P7 rat blocked or delayed migration of gonocytes from the center of the seminiferous tubules to the basement membrane, delayed the formation of the germline stem cell pool, reduced proliferation of type A spermatogonia normally observed at P8, and induced germ cell apoptosis. They attributed all these events to the inhibition of c-kit.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of successive expression, disappearance, and reexpression of c-kit indicates that the timing of administration of a compound with multiple targets, such as imatinib, is critical to establish the identity of the affected molecule. The time interval selected by Nurmio et al (40) spans not only the period of the initial expression of c-kit by spermatogonia but also the period of expression of PDGFR-␤ by gonocytes. Thus, we strongly suspect that although the reduced proliferation of spermatogonia after imatinib administration from P5-P7 may be due to c-kit inhibition, the effect of imatinib on gonocytes should be assigned to the PDGFR-␤ blockage probably occurring during the first day of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents, compounds altering the balance of endogenous apoptotic and anti-apoptotic proteins (e.g. p53, Fas, and Bcl systems), [7][8][9] and compounds interfering with growth factors supporting spermatogonia (e.g., stem cell factor or its receptor c-kit) 10 can all cause spermatogonial death and loss across multiple species. [11][12][13] (also see Murphy and Richburg, this issue)…”
Section: Manifestations Of Toxicity On Germ Cellsmentioning
confidence: 99%
“…Flow cytometry has been used as a more data‐intensive method to study the behavior of the different testicular cell populations. A golden standard for flow cytometry analysis of testicular cells has been the use of stoichiometric DNA stains to study the different germ cell populations based on their DNA content (Toppari et al ., 1985, 1986, 1988; Nurmio et al ., 2007; Michaelis et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%